The Power of Being There for Each Other: The Importance of Self-Awareness, Identifying Stress and Burnout, and Proactive Self-Care Strategies for Sex-Offender Treatment Providers - Parsonson, Karen (International journal of offender therapy and comparative criminology, 2019)
This was an exploratory study which hypothesized that there would be significant individual differences in feelings, perceptions, experiences, self-care strategies, and barriers to practicing self-care between sex offender treatment professionals. Nine sex offender treatment providers, all female, received structured interviews. Experience with the population varied from 3 to 15 years. Qualitative data were evaluated for themes in perceived context and nature of their work. The focus was upon conceptualization of self-care and implications, both professionally and personally. Three areas of self-care strategies emerged: personal, professional, and organizational. Perspectives differed with years of experience, with differential impacts on each area. Barriers were found to practicing self-care at all levels. To maintain well-functioning, it is suggested that there is an individual goodness of fit. Connection to others, however, appears to be extremely important, as does work-life balance. Recommendations include practicing regular self-care, as well as education about self-awareness and self-care during training.